Feeding the World : An Economic History of Agriculture, 1800-2000 - Federico, Giovanni, 1954- (Book collections on Project MUSE., 2009)
In the last two centuries, agriculture has been an outstanding, if somewhat neglected, success story. Agriculture has fed an ever-growing population with an increasing variety of products at falling prices, even as it has released a growing number of workers to the rest of the economy. This book, a comprehensive history of world agriculture during this period, explains how these feats were accomplished. Feeding the World synthesizes two hundred years of agricultural development throughout the world, providing all essential data and extensive references to the literature. It covers, systematica.